MHC class II invariant chain–adjuvanted viral vectored vaccines enhances T cell responses in humans - Esposito, I; Cicconi, P; D'Alise, AM; Brown, A; Esposito, M; Swadling, L; Holst, PJ; Bassi, MR; Stornaiuolo, M; Mori, F; Vassilev, V; Li, W; et al. (American Association for the Advancement of Science, 2020)
Strategies to enhance the induction of high magnitude T cell responses through vaccination are urgently needed. Major histocompatibility complex (MHC) class II–associated invariant chain (Ii) plays a critical role in antigen presentation, forming MHC class II peptide complexes for the generation of CD4+ T cell responses. Preclinical studies evaluating the fusion of Ii to antigens encoded in vector delivery systems have shown that this strategy may enhance T cell immune responses to the encoded antigen. We now assess this strategy in humans, using chimpanzee adenovirus 3 and modified vaccinia Ankara vectors encoding human Ii fused to the nonstructural (NS) antigens of hepatitis C virus (HCV) in a heterologous prime/boost regimen. Vaccination was well tolerated and enhanced the peak magnitude, breadth, and proliferative capacity of anti-HCV T cell responses compared to non-Ii vaccines in humans. Very high frequencies of HCV-specific T cells were elicited in humans. Polyfunctional HCV-specific CD8+ and CD4+ responses were induced with up to 30% of CD3+CD8+ cells targeting single HCV epitopes; these were mostly effector memory cells with a high proportion expressing T cell activation and cytolytic markers. No volunteers developed anti-Ii T cell or antibody responses. Using a mouse model and in vitro experiments, we show that Ii fused to NS increases HCV immune responses through enhanced ubiquitination and proteasomal degradation. This strategy could be used to develop more potent HCV vaccines that may contribute to the HCV elimination targets and paves the way for developing class II Ii vaccines against cancer and other infections.